Перетворювачі параметрів кондуктометричних сенсорів у напругу - Походило, Євген (Видавництво Національного університету «Львівська політехніка», 2002)
There are measuring transducers construction variants of conduction sensors parameters in voltage. Thert are schemes of transducers that provide an independence of converslon result from uninformative parameters of sensor.